RELATIONSHIP BETWEEN PARITY AND INFANT WEIGHT WITH BIRTH CANAL TEARING IN EMPAT LAWANG REGIONAL HOSPITAL - Maulidyanti, Anisah Tifani; Lastari, Fera Rika; Herdiyani, Tria Nopi (UNIVERSITAS AIRLANGGA, 2025)
Background: According to data from the World Health Organization (WHO), 2.7 million cases of perineal rupture occurred in mothers giving birth. This figure is estimated to reach 6.3 million in 2050. Ordinary perineal rupture can turn into a more severe case of perineal rupture and cause death in women giving birth if management is not carried out properly and responsively. This study aims to determine the relationship between parity and birth weight of babies with birth canal tears in mothers giving birth at Empat Lawang Regional Public Hospital, Empat Lawang Regency, Indonesia. Method:This study used an analytical survey with a case control design involving 72 mothers experienced a tear in the birth canal during October to November 2023, in the Obstetrics Room Empat Lawang Regional Public Hospital. Data collection analysis techniques use secondary data and analysis uses univariate and bivariate analysis, using chi-square. Results: The results showed that from 144 respondents, there were 72 respondents with birth canal lacerations, 66 respondents with primiparous or grandemultiparous parity, 71 respondents with birth weight <2500 gr or >4000 gr. There is a relationship between parity and birth canal tears at Empat Lawang Regional Hospital with a p-value of 0.000 <α 0.05. There is relationship between the birth weight of the baby and birth canal tears at Empat Lawang Regional Hospital with a p-value of 0.000 <α 0.05. Conclusion: There is a relationship between parity and baby weight with the incidence of birth canal tearing in mothers giving birth at Empat Lawang Regional Hospital.